The Relative Abundance Analysis of Microbial Community in the Baltic Sea - Sari, Tria Puspa (IJCONSIST JOURNALS, 2020)
The microbial community is important to control the sustainability of water ecosystems. The microbial community also has a negative impact on the environment. In particular, the toxin of Algae Bloom in the Baltic Sea which is harmful to the environment and humans. Several previous studies have tried various machine learning methods to analyze algae growth, but with limited achievement. The 167 samples were collected from 2012 to 2013 by the Linnaeus Marine Observatory at 11 km off the shore of Kårehamn in the Baltic Sea. Here we analyze the abundance of the microbial community using the Operational Taxonomic Units (OTUs) based on the normalization method after filtering samples. The aim to analyze the composition of the microbial community based on the past measurement of microbial composition. It is the pre-processing of data which is the step toward the prediction in the future. The result shows large different variations in each of OTUs in the fractions from the same sample. Many OTUs that are very abundant in one fraction but very rare in the other fraction. The Large difference abundance of OTU composition make a major challenge when predicting OTU composition in the future. Further quantification of normalization method is required in the pre-processing of data to get the proper data for prediction.